2023
DOI: 10.21037/qims-22-991
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cerebral blood perfusion on the correlation between cerebral stroke onset time and synthetic T2 mapping: a pilot study

et al.

Abstract: Background: In patients with acute stroke with an unknown onset time, the T2 relaxation time (qT2) in the region of diffusion restriction is associated with the time from symptom onset. We hypothesized that cerebral blood flow (CBF) status assessed using arterial spin labeling magnetic resonance (MR) imaging would influence the association between qT2 and stroke onset time. The purpose of this study was to preliminarily investigate the effects of diffusion-weighted imaging-T2-weighted fluid-attenuated inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…By analyzing signal intensity and region volume on T2-FLAIR images, quantitative metrics related to the severity of ischemic damage can be obtained to predict prognosis. Studies show correlations between stroke onset time and T2-FLAIR signal as well as its quantitative T2 relaxation time (qT2) changes (Wang et al, 2023). The difference and ratio in qT2 were correlated with the onset time in stroke patients in the 4.5 h window.…”
Section: T2-weighted Fluid-attenuated Inversion Recoverymentioning
confidence: 95%
“…By analyzing signal intensity and region volume on T2-FLAIR images, quantitative metrics related to the severity of ischemic damage can be obtained to predict prognosis. Studies show correlations between stroke onset time and T2-FLAIR signal as well as its quantitative T2 relaxation time (qT2) changes (Wang et al, 2023). The difference and ratio in qT2 were correlated with the onset time in stroke patients in the 4.5 h window.…”
Section: T2-weighted Fluid-attenuated Inversion Recoverymentioning
confidence: 95%
“…T2 relaxation time has been demonstrated to be affected by cerebral blood flow and collateral status ( 17 , 18 ). Wang et al ( 18 ) demonstrated that in patients with poor cerebral blood flow, T2 relaxometry correlated with stroke onset time, with no significant correlation in the group with good cerebral blood flow.…”
Section: Tissue-based Propertiesmentioning
confidence: 99%
“…T2 relaxation time has been demonstrated to be affected by cerebral blood flow and collateral status ( 17 , 18 ). Wang et al ( 18 ) demonstrated that in patients with poor cerebral blood flow, T2 relaxometry correlated with stroke onset time, with no significant correlation in the group with good cerebral blood flow. However, as T2 relaxometry is highly specific to tissue composition, there are limitations to this technique due to variability with anatomical location ( 59 ).…”
Section: Tissue-based Propertiesmentioning
confidence: 99%